Multiple risk factors and ischaemic stroke in the elderly Asian population with and without atrial fibrillation - Guo, Yutao; Wang, Hao; Tian, Yingchun; Wang, Yutang; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2016)
Ischaemic stroke risk rises with the increasing cardiovascular risk factors. How atrial fibrillation (AF) incrementally contributes to the risk for ischaemic stroke with increasing age and multiple cardiovascular risk factors is unclear. In an individual patient with AF the mechanism of ischaemic stroke may be related directly to AF itself or to risk factors associated with AF. It was this study’s objective to investigate incident ischaemic stroke in relation to age and increasing cardiovascular risk factor(s), and the incremental impact of AF on stroke rates. We studied a 5 % random sampling from Chinese medical insurance data covering more than 10 million individuals, for the years 2001 to 2012. The rate of ischaemic stroke was calculated amongst the individuals with no prior history of ischaemic stroke, in relation to age groups (aged < 65, 65–74,75 years old; n = 348,431, n = 56,952, n = 20,217, respectively), and increasing risk factors using the CHA2DS2-VASc score. Among the randomly sampled 425,600 individuals with total follow-up of 1,864,232 patient-years [63.8 % male, mean age 60 years; 880 with AF, vs 424,720 non-AF], there were 13,242 (3.1 %) ischaemic strokes after 64,834 person-years follow-up. Overall, ischaemic stroke incidence (per 100 person-years) was 0.35 (95 %CI 0.34–0.35) in the non-AF population and 1.11 (0.84–1.45) with AF. The AF population age < 65 and 65–74 had higher CHA2DS2-VASc scores than the nonAF population (p< 0.001), but this was non-significant between the non-AF and AF population age75 (p=0.086). For the population age75 years, incident stroke rates were 2.07 (0.86–4.76) and 4.29 (4.08–4.51) in non-AF and AF populations, respectively. The non-AF population age65 years with2 additional comorbidities (hyper-tension, vascular disease, diabetic, or heart failure) had ischaemic stroke rates similar to an AF population with CHA2DS2-VASc4. In both non-AF and AF populations, those with CHA2DS2-VASc =1 had a 1.9 fold increase in stroke risk, and those with CHA2DS2-VASc2 had more than four-fold increased risk for stroke, compared with those with CHA2DS2-VASc=0. In conclusion, an increasing cluster of multiple cardiovascular risk factors (besides AF) contributes to a greater risk for ischaemic stroke, especially in the elderly population. If elderly and with multiple risk factors, non-AF patients may have a risk of incident ischaemic stroke that is comparable or even higher than patients with AF, suggesting that the incremental stroke risk attributable to AF is marginal in such ‘high risk’ patients.
Keywords: Ischaemic stroke; cardiovascular risk factors; atrial fibrillation; elderly